Acts of Consumption: Spiritual and Material Food in The Towneley Plays - Sarah Lancaster (SELIM)
This discussion explores three plays from the Towneley collection, uniquely extant in San Marino, Huntington Library, HM 1, exploring their alimentary language within a context of late medieval holiday playing. Prima Pastorum, Secunda Pastorum and Mactacio Abel all contain verifiable references to a small area between modern Wakefield and Dewsbury. All feature language and imagery related to hunger, appetite, pleasure, satiation and digestion. Such references engage with the rituals of fasting, mass, procession and feasting which characterised feast-days, incorporating audiences’ somatic experiences into the devotional and didactic work demanded by Biblical drama. Two key aspects of the plays’ alimentary dramaturgy are discussed here: their use of food to produce feelings of spiritual joy, and their deployment of digestive metaphors to encourage thoughtful and engaged collective learning. As demonstrated below, this engagement with alimentation belies any polarising alignment of invisible food with the sacred and real food with the secular or profane.